AIE Luminogen‐Functionalized Hollow Mesoporous Silica Nanospheres for Drug Delivery and Cell Imaging. Issue 11 (25th January 2016) - Fan, Zhiying; Li, Dongdong; Yu, Xue; Zhang, Yuping; Cai, Yong; Jin, Jingji; Yu, Jihong
Abstract: Hollow mesoporous silica nanospheres functionalized with aggregation‐induced emission (AIE) luminogen tetraphenylethene were prepared by postgrafting method. The as‐prepared inorganic–organic hybrid nanospheres show bright blue emission and good biocompatibility as shown by MTT assays. The large cavities of the materials enable high loading of the anticancer drug doxorubicin hydrochloride (DOX), and the mesoporous silica shells allow pH‐dependent drug release. The materials can be effectively taken up by cells and function as luminescent bioprobes, demonstrating their potential application in imaging‐guided therapy. Abstract : Let it go : Aggregation‐induced emission (AIE) luminogen‐functionalized hollow mesoporous silica nanospheres with large void space and well‐defined mesopores show bright blue emissions under 365 nm UV irradiation. The obtained materials exhibit a pH‐dependent release of the anticancer drug doxorubicin hydrochloride (see scheme), and pose no toxicity to living cells; this demonstrates their potential application in imaging‐guided therapy.